2013
DOI: 10.1155/2013/214270
|View full text |Cite
|
Sign up to set email alerts
|

New Spectrophotometric and Conductometric Methods for Macrolide Antibiotics Determination in Pure and Pharmaceutical Dosage Forms Using Rose Bengal

Abstract: Two Simple, accurate, precise, and rapid spectrophotometric and conductometric methods were developed for the estimation of erythromycin thiocyanate (I), clarithromycin (II), and azithromycin dihydrate (III) in both pure and pharmaceutical dosage forms. e spectrophotometric procedure depends on the reaction of rose bengal and copper with the cited drugs to form stable ternary complexes which are extractable with methylene chloride, and the absorbances were measured at 558, 557, and 560 nm for (I), (II), and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
0
12
1
Order By: Relevance
“…The detection limits are lower than the reported methods 11,14 . These methods utilized a single step reaction with no extraction process and so simpler compared to reported methods 14,16 .…”
Section: Drugcontrasting
confidence: 54%
See 2 more Smart Citations
“…The detection limits are lower than the reported methods 11,14 . These methods utilized a single step reaction with no extraction process and so simpler compared to reported methods 14,16 .…”
Section: Drugcontrasting
confidence: 54%
“…It has been observed that, the BCG methods have wider linear ranges as compared to most of the reported methods [11][12][13][14] . These proposed methods are more sensitive compared to some of the established methods as shown by the molar absorptivity 11,14,17 . The detection limits are lower than the reported methods 11,14 .…”
Section: Drugmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the mentioned highly sophisticated detector, diode-array (DAD) [20,21], chemiluminescence [22], fluorescence [23] and electrochemical [3] detectors have also been used. Additionally, spectrophotometric and conductometric methods for the estimation of erythromycin thiocyanate in both pure and pharmaceutical dosage forms were developed [24].…”
Section: Introductionmentioning
confidence: 99%
“…HPLC method has been developed and validated by Trivedi and Patel [22] to measure the amount of Azin in pharmaceutical formulation. Sayed et al [23] developed spectrophotometric and conductivity methods for the estimation of Azin and other antibiotics in both pure and pharmaceutical forms. Sensitive and selective LC-MS methods were developed by Zuak et al [24] and validated for the quantification of Azin in human plasma.…”
Section: Introductionmentioning
confidence: 99%